Distribution and Relative Abundance of S100 Proteins in the Brain of the APP23 Alzheimer’s Disease Model Mice - Hagmeyer, Simone; Romão, Mariana A.; Cristóvão, Joana S.; Vilella, Antonietta; Zoli, Michele; Gomes, Cláudio M.; Grabrucker, Andreas M. (Frontiers in Neuroscience, 2019)
Increasing evidence links proteins of the S100 family to the pathogenesis of Alzheimer’s disease (AD). S100 proteins are EF-hand calcium-binding proteins with intra- and extracellular functions related to regulation of proliferation, differentiation, apoptosis, and trace metal homeostasis, and are important modulators of inflammatory responses. For example, S100A6, S100A8, and S100B expression levels were found increased in inflammatory diseases, but also neurodegenerative disorders, and S100A8/A9 complexes may provide a mechanistic link between amyloid-beta (Aβ) plaque formation and neuroinflammation. On the other hand, S100B, a proinflammatory protein that is chronically up-regulated in AD and whose elevation precedes plaque formation, was recently shown to suppress Aβ aggregation. Here, we report expression of S100A6 and S100B in astrocytes and less so in neurons, and low level of expression of S100A8 in both neurons and glial cells in vitro. In vivo, S100A8 expression is almost absent in the brain of aged wildtype mice, while S100A6 and S100B are expressed in all brain regions and most prominently in the cortex and cerebellum. S100B seems to be enriched in Purkinje cells of the cerebellum. In contrast, in the brain of APP23 mice, a mouse model for Alzheimer’s disease, S100B, S100A6, and S100A8 show co-localization with Aβ plaques, compatible with astrocyte activation, and the expression level of S100A8 is increased in neural cells. While S100A6 and S100B are enriched in the periphery of plaques where less fibrillar Aβ is found, S100A8 is more intense within the center of the inclusion. In vitro assays show that, similarly to S100B, S100A6, and S100A8 also delay Aβ aggregation suggesting a regulatory action over protein aggregation. We posit that elevated expression levels and overlapping spatial distribution of brain S100 proteins and plaques translates functional relationships between these inflammatory mediators and AD pathophysiology processes that uncover important molecular mechanisms linking the aggregation and neuroinflammation cascades.